Creating an engaging and stimulating anatomy lecture environment using the Cognitive Load Theory-based Lecture Model: Students' experiences - Siti N.H., Hadie; Husnaida, Abdul Manan @ Sulong,; Asma’, Hassan; Zul I., Mohd Ismail; Saiful, Talip; Ahmad F., Abdul Rahim (Elsevier BV, 2018)
Objective: There is a need to create a standard interactive anatomy lecture that can engage students in their learning process. This study investigated the impact of a new lecturing guideline, the Cognitive Load Theory-based Lecture Model (CLT-bLM), on students’ cognitive engagement and motivation.